Estimating gold-ore mineralization potential within Topolninsk ore field (Gorny Altai); IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Timkin T. V. Timothy Vasilyevich; Voroshilov V. G. Valery Gavrilovich; Асканакова О. Ю. Ольга Юрьевна; Cherkasova T. Yu. Tamara Yurievna; Chernyshov A.; Korotchenko T. V. Tatiana Valerievna (Ore Deposits. Current Prospecting and Exploration Methods, 2015)
Title screen